W poszukiwaniu teorii operacji specjalnej - Krystian Frącik (Przegląd Geopolityczny)
The analysis of the available sources shows that there are currently many different definitions of the term special operations, some of which contain an element of interpretation ambiguity, and most need to be more fully adequate to the current rules of their conduct. In modern literature, instructions and doctrines, both Englishlanguage and national, one can encounter interchangeably used expressions: special operations, special tasks or special actions. It is because the Polish Special Operation Forces are using documents based on English-language NATO originals, in which the term operation can be freely translated into Polish in at least several ways (actions, operations, operational activities). Therefore, it becomes necessary to put this terminological chaos in order, among other things, by attempting to identify and describe the theory of special operations.